2013
DOI: 10.1042/bst20130188
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in cytoplasmic dynein and its regulators cause malformations of cortical development and neurodegenerative diseases

Abstract: Neurons are highly specialized for the processing and transmission of electrical signals and use cytoskeleton-based motor proteins to transport different vesicles and cellular materials. Abnormalities in intracellular transport are thought to be a critical factor in the degeneration and death of neurons in both the central and peripheral nervous systems. Several recent studies describe disruptive mutations in the minus-end-directed microtubule motor cytoplasmic dynein that are directly linked to human motor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 83 publications
0
77
0
2
Order By: Relevance
“…Nde1 has been implicated in the regulation of the cytoskeleton and dynein motors (Lipka et al, 2013). However, it is unclear how such regulation could underlie the tissue specific and spatiotemporally dependent phenotype of both human and mouse NDE1/Nde1 mutations nor the DNA replication defects described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nde1 has been implicated in the regulation of the cytoskeleton and dynein motors (Lipka et al, 2013). However, it is unclear how such regulation could underlie the tissue specific and spatiotemporally dependent phenotype of both human and mouse NDE1/Nde1 mutations nor the DNA replication defects described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in microtubule-related genes encoding for microtubule-associated proteins (MAPs) (e.g., Tau), MT severing proteins (e.g., spastin), microtubule-based motor proteins (e.g., dynein, kinesin), and motor associated regulators (e.g., dynactin, doublecortin, and lis1) are associated with various neurodevelopmental problems (Lipka et al, 2013;Reiner and Sapir, 2013). In addition, impairment of axonal transport in mature neurons is a common factor in many of the major neurodegenerative diseases, including the motor neuron diseases amyotrophic lateral sclerosis (ALS) and Alzheimer's disease (Millecamps and Julien, 2013) and neuroinflammatory diseases such as multiple sclerosis (Sorbara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian BICD family proteins have been implicated in Rab6 secretory vesicle trafficking (Grigoriev et al, 2007;Matanis et al, 2002) and nuclear positioning (Splinter et al, 2010). Recent studies identified various mutations in the human BICD2 gene in patients with dominant congenital spinal muscular atrophy (Lipka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%